Liquefied natural gas storage tank simplified mechanical model and seismic response analysis. Issue 141 (February 2021) - Luo, Dongyu; Liu, Chunguang; Sun, Jiangang; Cui, Lifu; Wang, Zhen
Abstract: In this study, a scale model of a liquefied natural gas (LNG) storage tank was designed to carry out a shaking table test, the main position of insulation layer on tank and the site effect were investigated under different ground motions. The test results show that there is an obvious interaction between the insulation layer and the liquid-solid coupling position of the storage tank, and the seismic response of the tank was related to the frequency of the ground motions, the site effect should be considered when analysing the seismic response of liquid-solid coupling structures. Based on the test results, a simplified mechanical model for the seismic design of LNG storage tanks that considered the insulation layer was constructed, and the simplified mechanical model was verified via a numerical simulation method. Moreover, based on the results of the 16 × 10 4 m 3 LNG storage tank simplified mechanical model, the base shear and bending moment were reduced by 20%–25% on average, the acceleration and displacement of the inner tank wall were reduced by 40% on average after filling the insulation. In the seismic design of large scale LNG storage tanks, considering the damping effect of insulation is helpful to save design capital, and ignoring the damping effect of insulation will make the design conservative.